2011
DOI: 10.4172/2157-7099.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Induced Histological and Ultrastructural Alterations In Liver Tissue of Rat

Abstract: Background:Cisplatin is well-known anticancer drug often been used for treatment of various human malignancies. The hepatotoxic or nephrotoxic effect of drug is a result of altered histological and antioxidant status of the organ. In order to document the extent of cisplatin (CDDP) effect on liver we have studied long term treatment of cisplatin (CDDP) to rat. In our previous studies we have demonstrated changes in reduced glutathione (GSH) and glutathione related enzymes of liver followed by increased lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…These activated Kupffer cells had deteriorated cytoplasm and malformed nuclei having electrondense chromatin materials, as well as extended filopodia. The present findings are alongside with previous investigations carried out by Kamble & Bhiwgade (2011) and Kandil et al (2021).…”
Section: Ultrastructural Resultssupporting
confidence: 89%
“…These activated Kupffer cells had deteriorated cytoplasm and malformed nuclei having electrondense chromatin materials, as well as extended filopodia. The present findings are alongside with previous investigations carried out by Kamble & Bhiwgade (2011) and Kandil et al (2021).…”
Section: Ultrastructural Resultssupporting
confidence: 89%
“…The prevailing data revealed several lesions in the maternal liver of both groups II and III including ; vacuolation, apoptosis, an increase of the eosinophil's of some hepatocytes in the portal area, congestion of the central vein, and dilatation of the sinusoids. The current findings were comparable to the findings of those (22)(23)(24)(25)(26)(27), how indicates that injecting rodents (rats) with the platinum-base anticancer at certain doses can induce programmed cell death, and some structural changes in the liver. The current findings were contrary to the findings of (25).…”
Section: Discussionsupporting
confidence: 89%
“…Some area of the cytoplasm showed rarefaction, lipid droplets and vacuoles. Other investigators found some of these changes [30][31][32] .…”
Section: Discussionmentioning
confidence: 85%